Niborskiana: a new genus to accommodate Tigava gracilis Monte and Tigava notabilis Drake (Hemiptera: Heteroptera: Tingidae) - Montemayor, Sara I. (Zootaxa, 2012)
A new Neotropical genus, Niborskiana n. gen., is introduced to accommodate Tigava gracilis Monte and T. notabilisDrake, and redescriptions, illustrations and photographs of these two species are provided. A diagnosis for the genus Tigava and a key to the related Neotropical genera are presented.